Flood mapping of Yialias river catchment area in Cyprus using Alos Palsar radar images - Tymvios, Filippos S.; Alexakis, Dimitrios; Themistocleous, Kyriacos; Retalis, Adrianos; Michaelides, Silas; Pashiardis, Stelios; Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2012)
This study strives to highlight the potential of flood inundation monitoring and mapping in a catchment area in Cyprus (Yialias river) with the use of radar satellite images. Due to the lack of satellite data acquired during dates flood inundation events took place, the research team selected specific images acquired during dates that severe precipitation events were recorded from the rain gauge station network of Cyprus Meteorological Service in the specific study area. The relationship between soil moisture and precipitation was thoroughly studied and linear regression models were developed to predict future flood inundation events. Specifically, the application of fully polarimetric (ALOS PALSAR) and data acquired over different dates for soil moisture mapping is presented. The PALSAR (Phased Array type L-band Synthetic Aperture Radar) sensor carried by the ALOS (Advanced Land Observing Satellite) have quadruple polarizations (HH, VV, HV, VH). The amount of returned radiation (as backscatter echoes) that dictates the brightness of the image depends on factors such as the roughness, size of the target relative to the signal's wavelength, volumetric and diffused scattering. The variation in soil moisture pattern during different precipitation events is presented through soil moisture maps obtained from ALOS PALSAR and data acquired during different dates with different precipitation rates. Soil moisture variation is clearly seen through soil moisture maps and the developed regression models are used to simulate future inundation events. The results indicated the considerable potential of radar satellite images in soil moisture and flood mapping in catchments areas of Mediterranean region. 2012 SPIE.
Keywords: Soil surveys; Advanced land observing satellites; Land cover; Landscape metrics; Linear regression models; Mediterranean region; Phased array type l-band synthetic aperture radars; Precipitation events; Soil moisture mapping; Agriculture; Catchments; Classification (of information); Ecosystems; Flood control; Floods; Mapping; Mathematical models; Radar; Regression analysis; Remote sensing; Runoff; Satellite imagery; Soil moisture; Textures